2019
DOI: 10.1016/j.joto.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of outcomes of hearing and speech rehabilitation in children with cochlear implantation

Abstract: Objectives This study aimed to assess the effect of hearing and speech rehabilitation in patients with Nurotron ® cochlear implants. Design Ninety-eight paediatric patients with bilateral severe-to-profound sensorineural deafness who received cochlear implantation were divided into three groups according to age: group A (≤3 years), group B (4–7 years), and group C (8–16 years). All patients were followed up for one year for hearing and speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
(26 reference statements)
2
11
0
6
Order By: Relevance
“…This suggests that aural rehabilitation is effective for children with cochlear implants because the rate of development during the intervention was greater than the rate of development during the pre-intervention. In accordance with this finding, the study by Li et al, 22 on the outcomes of facilitated aural rehabilitation for children with cochlear implants mentioned an improved rate of auditory comprehension development after implantation. 22 Geers et al, 23 suggested that the implementation of aural rehabilitation after cochlear implantation facilitates access by hearing−impaired children to age−appropriate spoken language levels.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This suggests that aural rehabilitation is effective for children with cochlear implants because the rate of development during the intervention was greater than the rate of development during the pre-intervention. In accordance with this finding, the study by Li et al, 22 on the outcomes of facilitated aural rehabilitation for children with cochlear implants mentioned an improved rate of auditory comprehension development after implantation. 22 Geers et al, 23 suggested that the implementation of aural rehabilitation after cochlear implantation facilitates access by hearing−impaired children to age−appropriate spoken language levels.…”
Section: Discussionsupporting
confidence: 65%
“…In accordance with this finding, the study by Li et al, 22 on the outcomes of facilitated aural rehabilitation for children with cochlear implants mentioned an improved rate of auditory comprehension development after implantation. 22 Geers et al, 23 suggested that the implementation of aural rehabilitation after cochlear implantation facilitates access by hearing−impaired children to age−appropriate spoken language levels. 23 In the present study, a remarkable decline in the PCI was seen during the aural rehabilitation program.…”
Section: Discussionsupporting
confidence: 65%
“…The post CI rehabilitation such as AVT, regular mapping and troubleshooting are very crucial following the "switch-on" of the speech processor for a better outcome and mainstreaming of affected children to the society [1,13,14]. Through regular mapping, the audiologist used to provide optimal current level which helps in development of auditory sensation [15,16]. The current study has demonstrated the psychological impact (both to the CI recipients and parents) consequent to COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 74%
“…It was reported extensively in the literature that for a successful outcome with CI, continuous usage of the speech processor is critical 9 11 . In addition, optimal current levels are necessary for the development of auditory sensation 12 , 13 . It is also evident from the current study that the present situation is psychologically pressing for both parents as well as for their children.…”
Section: Discussionmentioning
confidence: 99%